Functional diversity of evertebrates in different types of beech forest in southern Sweden - Larsson,Martin (2014)
Abstract Deforestation, fragmentation and loss of biodiversity, all are elements that are common today. With this project I want to evaluate if there is a difference in functional diversity of evertebrates between beech stands of low herb and shrub type beech forest. I also want to test if there is a difference within tested areas between low herb and shrub type forests, but also if here is a difference between tested areas with the same forest type. I sampled leaf litter in beech forests in Skane, southernmost Sweden. Litter dwelling evertebrates were identified down to family level and their functional role in the system was written down after closer inspection of each family. Their abundance was also written down in my field notes. Later on the notes were used for calculations to get the richness data, the Shannon-Weiner diversity index and the functional diversity. The species to area relation was also tested through a linear regressions analysis. The carnivores were the most common functional group, and it was the only group that differed significantly between forest types (more common in shrub type forests). The functional diversity proved to be higher in the shrub type of forest, when compared to the herb type forest, but there was no significant difference in taxonomical diversity (analysed on the family level). There were no significant difference in the diversity between sites, within each forest type. I did not find any significance when comparing the functional levels between sites. Functional diversity did not differ between sites and there was no significant relation between functional diversity and the size of tested areas. The taxonomic diversity did not indicate any significant difference between forest types. Therefore, I did not find any support for my hypothesis that size of the sites or presence of an additional food level in low herb type forests gave any significant responses. What I learned was that there generally is not any significant difference in community structure when it comes to the functional diversity of detrivores, herbivores, omnivores, parasites or scavengers. This may indicate that beech forests are homogeneous habitats with only small differences in functional composition across the two forest types and the different sites.